Artemys. (Brussel : Artemys, 1985)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : Chaussée d'Ixelles 249, 1050 Bruxelles ; vanaf (1987) 8 Galerie Bortier 8-10, 1000 Bruxelles
Frans
Periodiek